Strategic investment with positive externalities - Jan-Henrik Steg; Jacco J. J. Thijssen (Bielefeld University, Center for Mathematical Economics (IMW), 2022)
We study strategic investment in continuous time with positive externalities of changing magnitude. Our model particularly allows for two correlated risk factors. Constructing subgame-perfect equilibria with pure and mixed strategies, we observe the novel effect that it is important for the firms to anticipate preemption. In fact, the presence of a second risk factor implies also an additional strategic risk. We quantify the associated extra waiting cost and show that it is ex ante uncertain whether investment will happen when there is a first- or a second-mover advantage. Our formal arguments involve several methodological contributions. In addition, we provide detailed specifications of our basic model to address various applications.
urn:nbn:de:0070-pub-30049110
Keywords: C61; C73; D21; D43; L13; 330; Real options; Externalities; Preemption; War of attrition; Optimal stopping; Multidimensional